If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 9 = 3(3x + 2) Reorder the terms: 9 + 10x = 3(3x + 2) Reorder the terms: 9 + 10x = 3(2 + 3x) 9 + 10x = (2 * 3 + 3x * 3) 9 + 10x = (6 + 9x) Solving 9 + 10x = 6 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 9 + 10x + -9x = 6 + 9x + -9x Combine like terms: 10x + -9x = 1x 9 + 1x = 6 + 9x + -9x Combine like terms: 9x + -9x = 0 9 + 1x = 6 + 0 9 + 1x = 6 Add '-9' to each side of the equation. 9 + -9 + 1x = 6 + -9 Combine like terms: 9 + -9 = 0 0 + 1x = 6 + -9 1x = 6 + -9 Combine like terms: 6 + -9 = -3 1x = -3 Divide each side by '1'. x = -3 Simplifying x = -3
| x^4-10x^2+40=0 | | U-3/u-2=4/u+4 | | 59x=-2-1+3 | | v+5/6v-1/6=(3/8v+1/4) | | -6(n+2)+13=-3n-8 | | 5g+11=-3 | | -2x+10-4=6 | | 2x^3+27=0 | | 2/3x-1/4+4/3x+3/4=6 | | 2(5c-1)-5=(8c+5) | | 4-1/2d=10 | | 3x+2x=5+3x | | N+2n=30 | | 6x+4x=74 | | 4.0=8.4/X | | 6(a-6)=48 | | a^3x-9ax^3=0 | | (p-6)(p-7)=0 | | 3x+2x=5+3 | | 3(d-4)=15 | | 8=4c-4 | | 4x+7,x=6 | | 6r+6=21r+9 | | y=2140x-53500 | | 47=11+12W | | 3/4+10=190 | | 8y+5x-3y+7-2x= | | 2x-5=4x-1+5 | | log[9]x=log[9]5+log[9]6-log[9]3 | | -5(1+2w)=20 | | 4x-16+6=2x+-6+2x | | 2-4x=-62 |